Estabilizaciones transitorias y permanentes usando al tipo de cambio o la cantidad de dinero como anclas nominales - Mariano Fernández (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
– This paper analyzes the results of some price stabilization programs classified in the literature as Exchange Rate Based Stabilization (ERBS) and Money Based Stabilization (MBS) in connection to their temporary nature for this, a theoretical and analytical framework is developed that allows differentiating each type of program and establishing under what conditions they are allowed to be classified as temporary and permanent. From that point on, their main characteristics are studied and conclusions are reached that are aligned with the theoretical consensus of this literature. The paper focuses primarily on stabilization programs in Argentina since early 1960s.
Keywords: E31; E42; E52; E58; F31; F32; 330; Inflacion; Desinflacion; Estabilizacion; Temporario; Permanente